Benefit sharing in the value chain of Indian mackerel Rastrelliger kanagurta in Karnataka: A policy perspective - Aswathy, N.; Rajesh, K. M.; Viswambharan, Divya; Rohit, Prathibha (Indian Journal of Fisheries, 2020)
Harvest and post-harvest activities in a multispecies multifleet unregulated marine fishery is highly complex involving a large number of intermediaries. The real economic benefits from fishing are often skewed in the hands of a few intermediaries in the value chain. Equitable distribution of benefits is an essential component for ensuringÂ sustainable exploitation and management in the context of ecosystem based management of marine fisheries. The present study analysed the market linkages and benefit sharing by different stakeholders in the value chain of Indian mackerel in Karnataka, south-west coast of India. Results of the study indicated that in terms of individual benefits, export processing and canning sectors in Karnataka grabbed a significant share in the Indian mackerel value chain and suggests a revisit into the policy on export incentives for Indian mackerel, in order to ensure equitable distribution of benefits among the stakeholders as well as to protect the interests of domestic consumers. Keywords: Benefit sharing, Indian mackerel, Policy perspective, Value chain